Calidad en el servicio ofrecido por los operadores de telefonía móvil en la ciudad de Iquitos, 2019 - Peña Rodríguez, Javier (2021)
The general objective of this research was to determine the quality of the service offered by mobile phone operators in the city of Iquitos, year 2019. Descriptive study and non-experimental design, for which a sample of 368 clients has been taken, being these respondents through a questionnaire as an instrument. The work concluded that, the quality of the service offered by mobile phone operators in the city of Iquitos is valued as fair, since Bitel is rated as fair with a tendency to be bad, likewise, Claro is rated as fair, Entel it is rated as bad with a tendency to be regular and Movistar is rated as good with a tendency to be regular. At the same time, the competition generated between Claro and Movistar has been evident, since they have great acceptance in the Iquiteño market, Claro despite maintaining deficiencies and some indicators of the quality of the service that show to be regular in the perception of its clients, shows strengths that can still exploit, however, Movistar having greater coverage for calls and internet in the area, is rated by a large percentage of its customers as good.